SANAD AND MATAN CRITICISM IN THE FRAMEWORK OF HADITH STUDIES - Nuril Muttaqin; Lestari Budianto; Nurun Najmi; Evi Dian Sari; Erdiyan Handoyo; Ahmad Safiq Mughni (JIEBAR : Journal of Islamic Education: Basic and Applied Research, 2023)
Sanad and matan criticism in the study of hadith science is a basic concept that needs to be understood and analyzed to strengthen belief in the quality and quantity of the hadith of the Prophet Muhammad. Sanad is a series of hadith narrators starting from friends who got it from Rasulullah to the last narrator. Meanwhile, matan is the content of the hadith itself. In particular, this research is expected to provide an understanding of sanad and matan criticism within the frame of hadith study, to determine the validity of hadith. Using a qualitative approach through library research, the author focuses on the object of the hadiths of the Prophet Muhammad. which have been collected in hadith books or books. The literature study in this research is based on various references, both in the form of books, journals, and articles that are relevant to the theme of the writing. The results of this study indicate that the criticism of sanad and matan within the framework of hadith science is a science that examines the origins of the hadith transmission, the entire narration in a hadith with the existing characteristics and forms, as well as the matan to determine the quality and quantity of hadith which in turn will determine whether a hadith can be accepted or rejected as evidence in Islamic law.